Design and development of web-based dental electronic medical records according to ministry of health standards - Erdianto Setya Wardhana; Suryono Suryono; Ari Hernawan; Lukito Edi Nugroho (Odonto : Dental Journal, 2023)
Background: Implementation of electronic medical records in health facilities is still very rare. The issuance of Regulation No. 24 of 2022 by the Minister of Health, which requires electronic medical records, means that all health facilities in Indonesia must be prepared to use electronic medical records. The results show that the format of electronic medical records, especially in dental facilities, is incomplete and non-standardized. Objective : The purpose of this study is to create an electronic medical record application for dentistry according to the standards of the Ministry of Health and works well. Method: The methods type is research and development with an action research approach. The method used to create the application is SDLC (Systems Development Life Cycle), which includes problem identification, design, application development, testing, implementation and maintenance. Result:, The results of dental electronic medical record system application has 100% complete formats according to the minimum requirements of the minister of health regulations, including patient identity formats, patient medical record formats, odontogram formats, medical treatment formats, supporting examination upload formats, and informed consent upload formats . Conclusion: This research has succeeded in creating an web-based application for an electronic medical record system for dentistry that has standard specifications of the Ministry of Health